Environmental chemistry : a comprehensive approach - Hanif, Muhammad Asif (Scrivener Publishing LLC : Wiley, 2020)
"This book is a very comprehensive project designed to provide complete information about environmental chemistry, including air, water, soil and all life forms on earth. The complete chemical composition and all the essential components of the atmosphere, hydrosphere, geosphere, lithosphere and biosphere are discussed in detail. Numerous forms of pollutants and their toxic effects along with sustainable solutions are provided. Not just covering the basics of environmental chemistry, the authors discuss many specific areas and issues, and they provide practical solutions. The problems of non-renewable energy processes and the merits of renewable energy processes along with future fuels are discussed in detail, making this volume a comprehensive collaboration of many other relevant fields which tries to fill the knowledge gap of all previously available books on the market. It also thoroughly covers all environment-related issues, internationally recognized standard values, and the socioeconomic impacts on society for the short and long term. A valuable reference for engineers, scientists, chemists, and students, this volume is applicable to many different fields, across many different industries, at all levels. It is a must-have for any library"- Resumé vydavatel
Includes index.
Keywords: environmentální chemie; environmental chemistry; elektronické knihy; monografie; electronic books; monographs